Frontispiece: Point Decoration of Silicon Nanowires: An Approach Toward Single‐Molecule Electrical Detection. Issue 20 (12th May 2014) - Wang, Jindong; Shen, Fangxia; Wang, Zhenxing; He, Gen; Qin, Jinwen; Cheng, Nongyi; Yao, Maosheng; Li, Lidong; Guo, Xuefeng
<x xml:space="preserve">Abstract</x> The real‐time, label‐free biodetection of H1N1 viruses with single‐molecule sensitivity by using Si nanowires as local reporters in combination with microfluidics is presented by M. Yao, L. Li, X. Guo et al. in their Communication on pp. 5038 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>